GPa-grade ultrahigh-strength anti-fatigue steel for ocean engineering and production method of GPa-grade ultrahigh-strength anti-fatigue steel

By using low carbon and low alloying and composite addition of multi-alloy reinforcement elements in marine engineering steel plates, the problems of low strength, poor low-temperature impact toughness, insufficient corrosion resistance and fatigue resistance are solved, and the existing steel plates are achieved. The comprehensive improvement of the high strength, excellent low-temperature toughness, good corrosion resistance and fatigue resistance of steel plates.

CN119433351AActive Publication Date: 2025-02-14ANGANG STEEL CO LTD

Patent Information

Application Number
CN202411567078.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

When facing complex marine environments, existing steel plates for marine engineering have low strength, poor low-temperature impact toughness, insufficient corrosion resistance and fatigue resistance.

Method used

Low carbon and low alloying are used as the basic characteristics, and the reinforcement elements of multi-alloys such as Mo, Cr, Ni, Co, and precipitation reinforcement elements such as V and N are added, and elements such as P, Al, Sb, and RE are added to optimize the chemical composition of the steel plate and Production technology, including converter smelting, LF refining, continuous casting and rolling.

Benefits of technology

It significantly improves the strength, low-temperature toughness, corrosion resistance and fatigue resistance of the steel plate, and meets the multiple requirements of marine engineering for high strength, excellent low-temperature toughness, good corrosion resistance and fatigue resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The GPa-grade ultrahigh-strength anti-fatigue steel comprises the following chemical components in percentage by weight: 0.02 to 0.07 percent of C, 0.10 to 0.25 percent of Si, 1.75 to 2.50 percent of Mn, 0.022 to 0.026 percent of P, less than or equal to 0.008 percent of S, 0.03 to 0.04 percent of Nb, 0.09 to 0.15 percent of V, 0.045 to 0.055 percent of Ti, 0.50 to 0.80 percent of Mo, 2.00 to 2.40 percent of Cr, 8.0 to 10.0 percent of Ni, 8.0 to 12.0 percent of Co, 0.035 to 0.045 percent of Als, 0.013 to 0.014 percent of N, 0.58 to 0.62 percent of Cu, 0.03 to 0.05 percent of Sb, 0.03 to 0.05 percent of RE and 0.0008 to 0.001 percent of B. The method comprises the steps of smelting, continuous casting, rapid cooling, casting blank heating, rolling and heat treatment. The maximum thickness of the steel plate is 100mm, Rp0.2 is 1080-1120MPa, A is greater than or equal to 18%, and the fatigue life gt under the peak stress of 560MPa; the impact energy at-60 DEG C is greater than or equal to 150J, and the marine atmosphere corrosion resisting rate is 1t; and 0.10 mm / a. The strength of the steel is improved, the impact toughness of the steel plate at low temperature is improved, and the corrosion resistance and the fatigue resistance of the steel are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation, and particularly relates to a GPa-level ultra-high-strength fatigue-resistant marine engineering steel and a production method thereof. Background Art

[0002] The ocean contains strategic resources such as oil, gas, combustible ice and minerals needed for the future development of human society. According to the situation faced by China's marine science and technology, the needs of coastal social and economic development, and the current status of marine science and technology work, my country has proposed a strategy to strengthen marine science and technology to support the development of deep-sea resources. The research focuses include the exploration and development of marine wind energy, marine oil and gas, combustible ice, the mining of ocean metal mineral resources, and the research and development of on-site efficient extraction technology and related equipment. When facing complex marine environments such as waves, temperature, humidity and salinity, steel used in marine equipment manufacturing requires steel to have higher corrosion resistance and fatigue resistance. If it has higher strength, greater thickness, good Z-direction performance, and better low-temperature impact toughness, corrosion resistance and fatigue resistance, it is difficult for existing steel to meet the above performance requirements at the same time. Therefore, it is necessary to manufacture a steel plate with high strength and excellent low-temperature toughness, corrosion resistance and fatigue resistance.

[0003] The patent "A 1GPa-grade marine engineering steel plate with excellent low-temperature toughness and its preparation method", application number 202011576945.X, discloses a 1GPa-grade marine engineering steel plate with excellent low-temperature toughness and its preparation method. Its designed chemical composition is combined with controlled rolling + multi-step heat treatment process to achieve the production of steel plates with high strength, low yield ratio and excellent low-temperature toughness. The obtained steel plate has a high yield rate, stable strength and low-temperature toughness, and has the characteristics of ultra-high strength (yield strength ≥ 1GPa), low yield ratio (<0.94), and excellent low-temperature toughness (-80℃ impact energy ≥ 150J), but it can only produce a thickness of 10 to 50 mm, and does not involve corrosion resistance and fatigue resistance.

[0004] The patent "960MPa grade quenched and tempered steel plate with excellent toughness and plasticity and its manufacturing method", patent number ZL201010227961.8, although the comprehensive mechanical properties of the disclosed steel plate have reached a relatively high level, with tensile strength ≥980MPa, yield strength ≥890MPa, and -60℃ Charpy transverse impact energy (single value) ≥47J, its strength is relatively low and does not involve corrosion and fatigue performance evaluation.

[0005] The patent "A FH690-grade marine engineering steel with excellent low-temperature toughness and its manufacturing method", application number 202110788240.2, discloses a FH690-grade marine engineering steel with a maximum thickness of 50mm and excellent low-temperature toughness and its manufacturing method. The steel plate has a yield strength of ≥690MPa, a tensile strength of 770-940MPa, an elongation after fracture of ≥14%, and a low-temperature toughness of -60℃ impact energy of ≥100J. However, its maximum thickness is only 50mm, and the corrosion resistance problem has not been solved, which cannot meet the needs of marine engineering construction.

[0006] The patent "A corrosion-resistant steel plate resistant to the South China Sea marine environment and its production process", application number: CN201410036368.3, provides a corrosion-resistant steel plate resistant to the South China Sea marine environment and its production process. The production process includes a converter smelting process, an LF refining process, a vacuum degassing process, a continuous casting process, and a controlled rolling and controlled cooling process. The organizational type of the steel plate is theoretically a single-phase polygonal ferrite fine structure (average grain size 10.17μm). In actual industrial production, it inevitably contains a very small amount of pearlite structure. Compared with conventional hull structural steel EH36, its corrosion resistance in marine environment (marine atmosphere, tidal range, full immersion, etc.) is improved by more than 50%, and it has good strength-toughness matching and welding performance, but its strength is low, its low-temperature toughness is insufficient, and its fatigue resistance has not been evaluated.

[0007] The patent "A yield strength 345MPa grade high fatigue structural steel and its manufacturing method", application number: 201910712227.1, discloses a yield strength 345MPa grade high fatigue structural steel, whose chemical composition is, C: 0.13% ~ 0.16%, Mn: 1.30% ~ 1.60%, Nb: 0.020% ~ 0.050%, Alt: 0.020% ~ 0.030%, Ti ≤ 0.010%, Si ≤ 0.12%, P ≤ 0.010%, S ≤ 0.005%, the remainder is iron and unavoidable impurities, and the large reduction + controlled cooling process is adopted. The obtained steel plate has good comprehensive mechanical properties and good surface quality, but the steel plate has low strength, and its corrosion performance is not evaluated. Only the impact toughness at -20℃ is evaluated, which is far from meeting the use requirements of different marine environments.

[0008] The patent "A corrosion-resistant fatigue steel for engineering and its preparation method", application number: 202110068169.0, discloses a corrosion-resistant fatigue steel for engineering. The steel is based on the main elements of E690 steel (C: 0.04%~0.07%, Si: 0.20%~0.26%, Mn: 1.45%~1.60%, P≤0.01%, S≤0.015%, Cr: 0.44%~0.50%), and element regulation and characteristic element addition are carried out. Among them, Cu: 0.28%~0.66%, Ni: 0.76%~1.55%, Sb: 0.03%~0.12%, and the rest are Fe and unavoidable impurities. Its corrosion fatigue strength can be increased by up to 52%, but the low-temperature toughness of the steel is not evaluated. Summary of the invention

[0009] In view of the shortcomings of the prior art, the purpose of the present invention is to propose a GPa-level ultra-high-strength and fatigue-resistant marine engineering steel and a production method thereof, which is characterized by low carbon and low alloying, compositely adding multi-element alloy strengthening elements such as Mo, Cr, Ni, Co and precipitation strengthening elements such as V and N, and adding P, Al, Sb and RE as basic characteristics, thereby improving the strength and low-temperature toughness of the steel plate, and having good corrosion resistance and fatigue resistance, thereby solving the problems of low strength, poor low-temperature impact toughness, insufficient corrosion resistance and fatigue resistance of existing marine engineering steel plates.

[0010] The present invention is characterized by a steel plate having excellent low temperature toughness, high strength, corrosion resistance and fatigue resistance. In the present invention, the chemical composition of the steel plate comprises C: 0.02% to 0.07%, Si: 0.10% to 0.25%, Mn: 1.75% to 2.50%, P: 0.022% to 0.026%, S: ≤ 0.008%, Nb: 0.03% to 0.04%, V: 0.09% to 0.15%, Ti: 0.045% to 0.055%, Mo: 0.50% to 0.80%, Cr: 2.00% to 2.40%, Ni: 8.0% to 10.0%, Co: 8.0% to 12.0%, Als: 0.035% to 0.045%, N: 0.01% to 0.03%, and V: 0.09% to 0.15%. .013%~0.014%, Cu: 0.58%~0.62%, Sb: 0.03%~0.05%, RE: 0.03%~0.05%, B: 0.0008%~0.001%, among which 0.08≤(Nb+V+Ti) / Mn≤0.12, 2.5≤Si / Al≤7.0, 3.5≤(Cu+Co) / Cr≤5.5, 12Cr / Co≥2.2, 3.2≤Ni / Cr≤4.5, 36Nb / Mn≥0.5, (Nb+V+Ti+Als) / N≥15, Ni / Cu≥13, (Nb+V+Ti) / RE≥4.2, RE / P≥1.10, and the rest are Fe and unavoidable impurities.

[0011] The present invention selects the above alloying element types and their contents because of the role of each element in improving the strength, toughness, corrosion resistance and fatigue resistance of marine engineering steel:

[0012] C: C and Cr can form alloy cementite (Fe·Cr)3C, and can also form carbides, such as Cr7C3, Cr 23 C6, etc., the melting point, hardness, wear resistance and stability of these carbides are higher than Fe3C, which can improve the strength of steel. C and strong carbide forming elements such as V, Nb, Ti, etc. will preferentially form carbides such as VC, NbC, TiC, etc., which have the highest stability, melting point, hardness and wear resistance. C is the most effective element to improve the strength of steel plates. When its content is lower than 0.02%, the strength of the steel plate will be greatly reduced, but C has a great influence on the low-temperature toughness, elongation and weldability of steel. From the perspective of improving the toughness, corrosion resistance, fatigue resistance and weldability of steel, the C content in steel should be controlled to be appropriately lower. Therefore, the C content of the present invention is selected to be 0.02% to 0.07%.

[0013] Si: Si is a necessary element for steelmaking deoxidation and has a certain solid solution strengthening effect. Although Si can improve the strength of steel plates, Si reduces the critical cooling rate of martensitic phase transformation, seriously damaging the low-temperature toughness, elongation and weldability of ultra-high strength steel plates. Si not only promotes the formation of MA islands, but also the size of the formed MA islands is relatively large and unevenly distributed, which seriously damages the toughness of the welding heat affected zone (HAZ). Therefore, the Si content in steel should be controlled as low as possible. A certain Si content can effectively improve the marine corrosion resistance of steel, and the composite addition of Si and Al can improve the corrosion resistance and high-temperature oxidation resistance. The Si content of the present invention is controlled at 0.10% to 0.25%, 2.5≤Si / Al≤7.0.

[0014] Mn: Mn is the main element for improving strength and toughness, and can significantly improve the hardenability of steel. It is very cheap and is the main additive element in steel. When the C content is low, a higher Mn content can effectively improve the hardenability of steel, improve the strength of the steel plate by refining the structure and promoting bainite transformation, and at the same time have excellent low-temperature toughness. Mn expands the austenite region and promotes grain enlargement, so it is necessary to add grain-refining elements Nb, V, and Ti in combination to promote grain refinement and improve the fatigue performance of steel. However, Mn is prone to segregation during the solidification of molten steel, which aggravates the segregation and looseness of the center of the ingot, resulting in low low-temperature toughness of ultra-high strength steel plates and cracks in welded joints, which need to be improved by optimizing the continuous casting process and heating process. The content of Mn in the present invention is selected to be 1.75% to 2.50%, and 0.08≤(Nb+V+Ti) / Mn≤0.12.

[0015] P: P has a strong solid solution strengthening effect in steel. When added as an alloying element to low alloy structural steel, it can improve its strength and atmospheric corrosion resistance. When its content is ≥0.02%, it can significantly improve the corrosion resistance. However, when its content is too high, it will have an adverse effect on the low temperature toughness of the parent material and the toughness of the welding heat affected zone. Therefore, its content should be controlled within a reasonable range as much as possible. The P content of the present invention is controlled at 0.022% to 0.026%.

[0016] S: S segregates seriously in steel, which deteriorates the quality of steel. S is an inclusion-forming element, forming inclusions such as FeS and MnS, which reduces the ductility of steel. The area near the inclusions will become the source of corrosion, which is not conducive to the corrosion resistance of the steel plate. FeS is easy to melt at the grain boundary due to its low melting point, which weakens the bonding force between grains and causes hot brittleness of steel. A certain amount of Mn element should be added to form MnS with a higher melting point and deformation ability. Therefore, the S content of the present invention should be ≤0.008%.

[0017] Co: Co plays a major role in solid solution strengthening in steel, improving the oxidation resistance and corrosion resistance of steel. Co can increase the interaction between Fe atoms, reduce the critical concentration of Cr atoms forming clusters, and thus improve the stability of Cr atom clusters. When Co and Cr atoms act on steel at the same time, a smooth passivation film is formed on its surface, which has a high structural stability and can well protect the matrix, thus having excellent corrosion resistance. Co improves strength and toughness by promoting more (Ti, Al) Ni3 precipitation nucleation hardening. The addition of Co has little effect on the precipitation ratio of Ni and Ti, but can reduce the size of the precipitated phase. Co increases the nucleation rate of Ni3Ti and increases the number density of the precipitated phase, that is, Co can make the distribution of the precipitated phase more dispersed, improve the fatigue resistance of steel, and enhance the precipitation strengthening effect of the precipitated phase. The Co content of the present invention is controlled at 8% to 12%, and 12Cr / Co≥2.2.

[0018] Mo: In quenched and tempered steel, Mo can make parts with larger cross-sections quenched deeply and hardened thoroughly, improve the tempering resistance or tempering stability of steel, and allow parts to be tempered at higher temperatures, thereby more effectively eliminating (or reducing) residual stress and improving plasticity. Mo can improve the corrosion resistance to organic acids (such as formic acid, acetic acid, oxalic acid, etc.) and hydrogen peroxide, sulfuric acid, sulfurous acid, sulfates, acid dyes, bleaching powder solution, etc. The addition of Mo prevents the pitting corrosion tendency caused by the presence of chloride ions and can improve the intergranular corrosion resistance of Cr and Ni steels. However, too high Mo will make the steel embrittled, reduce strength and plasticity, and deteriorate toughness. Therefore, the Mo content of the present invention is controlled at 0.50% to 0.80%.

[0019] Cr: Cr can improve the strength and hardness of steel. Cr is a ferrite-forming element, which helps to increase the ferrite content in steel and thus improve the low-temperature toughness of steel. Cr is an element that improves the corrosion resistance of steel, but adding Cr alone sometimes reduces the corrosion resistance, and even has a lower corrosion resistance than ordinary carbon steel. It needs to be used in combination with other corrosion-resistant alloying elements, such as Cu, P, Co, etc., to significantly improve its corrosion resistance. The Cr content of the present invention is controlled at 2.0% to 2.4%, and 3.5≤(Cu+Co) / Cr≤5.5.

[0020] Ni: Ni strengthens ferrite and refines pearlite in steel. The overall effect is to improve strength, and the effect on plasticity is not significant. Ni can improve the fatigue resistance of steel and reduce the sensitivity of steel to notches. Therefore, Ni can improve the fatigue performance of steel. Ni does not form carbides, and can strengthen ferrite by forming a simple substitutional solid solution. It also has the effect of reducing the toughness-brittleness transition temperature of steel and improving the low-temperature toughness of steel. A certain Ni content can ensure that the steel plate has sufficient hardenability and uniform performance in the thickness direction, while ensuring the strength and toughness matching and low-temperature toughness of the steel plate. Adding Ni to steel can also reduce the copper brittleness of Cu-containing steel, reduce intergranular cracking during hot rolling, and improve the atmospheric corrosion resistance of the steel plate. The combination of Ni and Cr can significantly improve the corrosion resistance of steel. The Ni content of the present invention is controlled at 8.0% to 10.0%, 3.2≤Ni / Cr≤4.5, and Ni / Cu≥13.

[0021] Cu: Cu is the most important and most commonly used alloying element in corrosion-resistant steel. Cu can activate the cathode, promote the passivation of the steel anode and slow down the corrosion. A copper-rich phase will form on the surface of the steel during the corrosion process. There is a dense and highly adherent intermediate layer between the surface corrosion layer and the copper-rich layer of the steel, which can further alleviate the corrosion of the steel. In particular, when used in combination with P, it can significantly improve the performance of resisting marine atmospheric corrosion and seawater corrosion. In addition to reducing the copper embrittlement of copper-containing steel and reducing the intergranular cracking effect during the hot rolling process, the composite addition of Cu and Ni is more importantly austenite stabilizing elements. The composite addition of Cu and Ni can significantly reduce Ar3 and increase the driving force of the phase transformation from austenite to ferrite. At the same time, copper can accelerate the high-temperature strain-induced precipitation of niobium carbonitride and increase the recrystallization stop temperature, which is conducive to controlled rolling in the non-recrystallization zone to refine the phase transformation products and improve the fatigue resistance of the material. The Cu content of the present invention is controlled at 0.58% to 0.62%.

[0022] Nb: Nb is an important element in controlled rolling and controlled cooling steel. Nb is a strong carbide-forming element. The two-phase particles NbC and NbN formed with C and N are important elements in controlled rolling and controlled cooling steel. They can effectively refine the grains, thereby improving the strength and low-temperature impact toughness at the same time. The composite addition of Nb and Mn can effectively inhibit the recovery and recrystallization of austenite during the rolling process. On the one hand, it can increase the austenite recrystallization temperature, thereby increasing the rolling temperature and reducing the load of the rolling unit; on the other hand, it can effectively refine the phase transformation structure of the steel plate, thereby improving the strength and low-temperature impact toughness at the same time, and preventing the intergranular corrosion of the steel by the oxidizing medium. Nb can increase the solid solution amount of rare earth in steel, thereby improving the corrosion resistance of steel. The Nb content of the present invention is controlled at 0.03% to 0.04%, and 36Nb / Mn≥0.5.

[0023] V: V has a great affinity with O and N and is a strong carbide-forming element. Generally, VC has a high dispersion and is extremely stable, so it is conducive to deoxidation and degassing to obtain a dense fine-grained structure, improve the plasticity, toughness and strength of steel, and its impact performance and fatigue strength are higher than those of vanadium-free steel. It has high strength and high toughness at both high and low temperatures (<0°C). The high dispersion of VC prevents the coarse grains of the weld and improves the weldability of the steel. However, when heated to the melting temperature of VC, it will cause the steel crystals to grow strongly. When dissolved into a solid solution at a high temperature, the hardenability is increased. On the contrary, when it exists in the form of carbides, the hardenability is reduced. V increases the tempering stability of quenched steel and produces a secondary hardening effect. V can increase the solid solution amount of rare earth in steel, thereby improving the corrosion resistance of steel. The V content of the present invention is controlled at 0.09% to 0.15%.

[0024] Ti: Ti has a strong affinity with N, O, and C, and its affinity with S is stronger than that of Fe. Therefore, it is a good deoxidizing and degassing agent and an effective element for fixing N and C. Ti is a strong carbonitride-forming element. A trace amount of Ti can combine with N in steel to form TiN, which prevents the growth of austenite grains during soaking and in the heat-affected zone of welding, thereby improving weldability. TiC and TiN have strong binding force, are stable, and are not easy to decompose. They can only be slowly dissolved into the solid solution in steel when heated to above 1000°C, which can significantly control the growth of grains in the heat-affected zone of welding and improve the welding performance of the material. Therefore, Ti fixes N and S and forms TiN, which can significantly improve the plasticity and impact toughness of steel. Ti can increase the solid solution of rare earth in steel, thereby improving the corrosion resistance of steel, but Ti has a great affinity with N and O and is very easy to form TiN and TiO2. When the steel ingot is at a low temperature, more non-metallic inclusions and subcutaneous pores will be formed. Therefore, the titanium-containing steel must control the O content. The Ti content of the present invention is controlled at 0.045% to 0.055%.

[0025] N: Like C, N can be dissolved in Fe to form interstitial solid solution. N expands the austenite phase of steel and is a strong austenite forming element. It can replace a part of Ni within a certain limit. N that penetrates into the surface of steel can be combined with Nb, Al, V, Ti and other elements to form extremely stable nitrides, thereby improving the corrosion resistance of steel. However, excessive residual N content in steel will lead to loose macroscopic structure or pore formation. Therefore, a certain amount of Al needs to be added to nitrogen-containing steel to form stable AlN to avoid defects such as nitrogen escape and pore formation during solidification. Therefore, the N content in the present invention is controlled at 0.013% to 0.014%, (Nb+V+Ti+Als) / N≥15.

[0026] Al: Al is mainly used for deoxidation and grain refinement. Al and N or O form effective fine dispersions to inhibit grain growth when steel is heated, and promote the decomposition of austenite when steel is cooled, thereby improving the hardenability of steel. It also acts as a nucleation point for recrystallization, promoting ferrite nucleation and grain refinement, and improving the fatigue resistance of steel. AlN itself has high stability when heated, so it can improve the thermal stability of steel, help reduce the overheating tendency of steel, and improve the oxidation resistance of steel. Al forms an effective surface hardening layer through the relatively low temperature diffusion (nitridation) of N, which improves the oxidation resistance and corrosion resistance of steel. When deoxidizing with Al, adding a certain amount of Si as appropriate can significantly improve the deoxidation of Al, but if the amount of Al is too much, it will cause abnormal structure and graphitization tendency of steel. Therefore, the Als content of the present invention is controlled to be 0.035% to 0.045%.

[0027] Sb: At austenite temperature, Sb in steel precipitates at MnS inclusions and along the original austenite grain boundaries, thereby inhibiting the enrichment and precipitation of MnS inclusions at the grain boundaries. Sb can also refine the size of secondary recrystallization grains, refine the structure of steel and improve toughness, thereby improving the fatigue resistance and corrosion resistance of steel. Sb helps to improve the corrosion resistance of materials. Adding Sb alone or in combination to steel significantly improves the corrosion resistance of materials. Sb forms a Sb2O5 corrosion-resistant oxide film on the surface of steel, which effectively prevents the interaction between the matrix and the corrosive medium and inhibits the corrosion of steel in the corrosive medium; Sb obtained after hydration 3+ The precipitates formed in the anode micro-area fill the corrosion cracks or cavities, improving the barrier to corrosion. - Penetration ability; Sb can also pass through Cl - Hydration in ambient media inhibits Fe 3+ Hydrolysis produces H + The process improves the pH value of the corrosion micro-area and alleviates the anodic dissolution process. Sb, as a corrosion inhibitor, changes the cathode and anode reaction process and can greatly improve the marine environment corrosion resistance of steel. The Sb content of the present invention is controlled at 0.03% to 0.05%.

[0028] RE: Rare earth (RE) atoms are active and have strong binding force. Adding RE to steel can improve solidification structure, change solid phase change structure, form harmless low melting point inclusions, strengthen interface through segregation, passivate surface rust layer, etc. RE can improve the self-corrosion potential and polarization resistance of weathering steel, thereby inhibiting the anode reaction, increasing the resistance of the entire electrochemical reaction, and significantly reducing the corrosion rate of steel; RE is enriched at the grain boundary through the diffusion mechanism, inhibiting the segregation of inclusions at the grain boundary, and improving the low temperature performance and corrosion resistance of steel; RE added to P-containing steel can reduce macrosegregation, reduce the segregation of P at the grain boundary and ferrite interface, and make the distribution of P in steel more reasonable, thereby significantly improving the toughness, corrosion resistance, fatigue resistance, etc. of steel, but rare earth is a scarce resource, and its addition amount must be controlled. The RE content of the present invention is controlled at 0.03% to 0.05%, (Nb+V+Ti) / RE≥4.2, RE / P≥1.10.

[0029] B: B has a strengthening effect on the grain boundary, can reduce the precipitates along the grain boundary, improve the grain boundary state, and the addition of B element ensures the hardenability of the steel plate without damaging the weldability, HAZ toughness and slab surface quality of the steel plate, which significantly improves the hardenability of the steel. Nb and B have a strong interaction, and the combined addition can increase the recrystallization temperature of the steel to above 950°C. At the same time, the synergistic effect of Ti and B is crucial to improving the impact toughness of the material. Ti is used to fix N in the steel, so that B is solid-dissolved in the steel. The B content of the present invention is controlled at 0.0008% to 0.001%.

[0030] The above are the content ranges and effects of adding various elements. The manufacturing method of the present invention for producing a high-performance anti-fatigue steel plate includes:

[0031] 1. The steel is smelted according to the above composition, and the process includes:

[0032] (1) During converter smelting, the contents of elements such as C, Si, Mn, P, and S are adjusted to be within the scope of the present invention. During the smelting process, the molten iron is first subjected to a desulfurization pretreatment, and the S content in the molten iron after desulfurization is ≤0.0025%. A top and bottom composite blowing process is adopted, and the converter tapping temperature is 1630-1650°C. After that, Si-Ca wire feeding treatment is performed, and the Ca content is controlled between 0.0015% and 0.0025%.

[0033] (2) Refining the molten steel, adding 20% ​​rare earth alloy (1.95-3.25 kg / ton steel) into the LF furnace 7-9 minutes before the end of vacuum treatment in the LF furnace, and then blowing argon for 5-10 minutes; then RH treatment is carried out, the RH treatment time is 30-35 minutes, and nitrogen is blown throughout the RH treatment to control [H] ≤ 1.0 ppm and [O] ≤ 20 ppm in the steel, and the net circulation time before removal is 6-10 minutes.

[0034] (3) Before the end of the RH treatment, add Sb element and ensure that the added amount is 1.2 to 1.3 times the target control amount to ensure that its endpoint content can be controlled within the target range.

[0035] 2. Cast the molten steel obtained in step 1 into the desired continuous casting billet. In order to control the content of equiaxed crystals in the continuous casting billet, the tundish is superheated at 20-30°C. A lower superheat can reduce the solidification time of the molten steel, reduce the segregation of elements such as C and Mn in the center of the billet, reduce defects such as looseness and shrinkage of the billet, and ensure the Z-direction performance and fatigue resistance of the steel plate; adopt full-process protection casting, the continuous casting billet drawing speed is controlled at 0.8-1.2m / min, and the secondary cooling water ratio is 0.80-1.0m 3 / t, so that the proportion of equiaxed crystals in the continuous casting billet is greater than 30.0%, and electromagnetic stirring is used at the end of solidification to make the molten steel evenly stirred and achieve high-strength and high-density solidification as soon as possible. Heavy pressure is used in the continuous casting process, and the pressure reduction is 15.0-20.0mm.

[0036] 3. In order to control the grain size of the continuous casting billet, the continuous casting billet is cooled rapidly, with the start cooling temperature of 950-1000°C and the cooling rate of 9.0-12.0°C / s. After cooling to 720-750°C, it enters the slow cooling pit for slow cooling. In order to reduce the internal stress of the continuous casting billet, the continuous casting billet is cooled to below 150°C at a cooling rate of 3.0-10.0°C / h.

[0037] 4. The continuous casting billet obtained in step 3 is sent to a heating furnace for heating. The heating adopts a segmented heating process, and the billet is put into the furnace at a furnace temperature of 600-650°C, and kept warm for 2.0-3.0 hours to release the internal stress of the billet; a slow heating process is adopted below 950°C to further release the internal stress caused by the continuous casting billet cooling and heavy pressure, and to prevent the temperature stress caused by too fast heating. The thermal rate is controlled at 6-8°C / min, and the billet is heated to 950°C and kept warm for 30-40 minutes; above 950°C, a process of rapid heating and appropriately extending the holding time is adopted to prevent the coarsening of austenite grains while allowing the alloy elements in the billet to fully diffuse and dissolve, further reducing element segregation, and the heating rate is controlled at 12-20°C / min, and the billet is heated to 1200°C-1220°C for uniform temperature, and the holding time is 2.0-4.0 hours.

[0038] 5. The ingot is rolled into a finished steel plate in two stages. In the first stage, in order to fully break the columnar crystals of the continuous casting ingot, a high-temperature slow rolling and large reduction process is adopted. The ingot is directly rolled after P removal. The rolling speed is 0.80-1.00 m / s. The reduction of each of the first three passes is ≥35 mm. During the rolling process, the billet is cooled by mill cooling water between each pass. The final rolling temperature is 1000-1030°C. The thickness of the warm billet is 1.5-2.0 times the thickness of the finished product. In order to inhibit the growth of the intermediate billet grains, the warm billet is cooled by water spraying at a cooling rate of 8.0-10.0°C / s until it is cooled to 15-25°C above the second stage rolling start temperature. The second stage rolling start temperature is 880-900°C, the rolling speed is 1.2-1.6 m / s, the final rolling temperature is 810-840°C, and then air-cooled to room temperature.

[0039] 6. After rolling, the steel plate is subjected to two quenching + tempering heat treatments, wherein the first quenching temperature is 870-900°C, the holding time is 1.2-1.5 min / mm, the second quenching temperature is 840-860°C, the holding time is 1.5-2.0 min / mm, the tempering temperature is 540-580°C, and the holding time is 2.5-3.5 min / mm. The effects of the two quenching processes are as follows: (1) The initial quenching can only make the steel surface reach a certain hardness, but through the second heating treatment, the inside of the steel can also reach the same hardness level, which makes the steel have better wear resistance and tensile strength, and improves the quality of the product; (2) After the initial quenching, a large amount of residual stress will be generated inside the steel, which is prone to deformation or cracking during use. The secondary quenching can eliminate these residual stresses and improve the organizational structure of the steel, making it more uniform and dense, which not only improves the service life of the product, but also reduces the adverse effects caused by stress; (3) The secondary quenching can effectively control the consistency of the internal organizational structure and performance of the steel, and ensure the stability of product quality; (4) Through the secondary quenching, finer grains will be formed inside the steel, thereby increasing the grain boundary area of ​​the steel and improving the low-temperature toughness of the steel.

[0040] The present invention adopts low carbon and high manganese content design, controls the range of composite alloying elements added to 0.08≤(Nb+V+Ti) / Mn≤0.12, 2.5≤Si / Al≤7.0, 3.5≤(Cu+Co) / Cr≤5.5, 12Cr / Co≥2.2, 3.2≤Ni / Cr≤4.5, 36Nb / Mn≥0.5, (Nb+V+Ti+Als) / N≥15, Ni / Cu≥13, (Nb+V+Ti) / RE≥4.2, RE / P≥1.10, improves the strength of steel, and ensures that the steel plate has excellent low temperature toughness, corrosion resistance and fatigue resistance. By optimizing the continuous casting process to control the influence of element segregation on the fatigue performance and low temperature performance of the steel plate, the heating adopts a slow and long-time segmented heating process, and the rolling adopts a high temperature, slow and large pressure reduction, non-crystallized zone rolling two-stage process, combined with the subsequent two quenching + tempering heat treatment processes. The strength of the steel plate is ensured by relying on fine grain strengthening, dislocation strengthening, solid solution strengthening and second phase strengthening; the good low-temperature toughness of the steel plate is ensured by relying on grain refinement; the good corrosion resistance of the steel plate is ensured by relying on oxides formed by elements such as Cr, Ni, and Co; the fatigue resistance of the steel plate is improved by controlling fine dispersed two-phase particles and element segregation; and the segregation of the P element is reduced by adding a small amount of Sb, RE and P elements in combination, thereby further improving the corrosion resistance of the steel plate.

[0041] 1. A composite addition of Mo, Co, Ni and Cr elements is proposed, and the steel plate has good comprehensive mechanical properties: yield strength 1080-1120MPa, elongation ≥18%, -60℃ impact energy ≥150J;

[0042] 2. A composite method of adding a small amount of Sb, RE and P elements is proposed to improve the corrosion resistance of the steel plate, and its marine atmospheric corrosion rate is <0.10mm / a;

[0043] 3. The steel plate has good fatigue resistance. Under the peak stress of 560MPa, the fatigue life is more than 2 million times;

[0044] 4. The thickness range that can be produced is wide, and the maximum thickness can reach 100mm. DETAILED DESCRIPTION

[0045] According to the above chemical composition and production process, the actual smelting composition of the present invention is shown in Table 1, the actual process parameters of the present invention are shown in Tables 2 to 6, and the actual properties are shown in Table 7.

[0046] Table 1 Melting composition, Wt%

[0047]

[0048] Table 2 Steelmaking process parameters

[0049]

[0050]

[0051] Table 3 Continuous casting process parameters

[0052]

[0053] Table 4 Heating process parameters

[0054]

[0055] Table 5 Rolling process parameters

[0056]

[0057]

[0058] Table 6 Heat treatment process

[0059]

[0060] Table 7 Physical properties

[0061]

[0062] As can be seen from Table 7, the yield strength of the steel plate with a thickness of 25 to 100 mm in the embodiment of the present invention is 1082 to 1118 MPa, all reaching the design strength of 1000 MPa or above, the elongation is 18.5% to 22.5%, and the impact energy at -60°C is 152 to 215 J, indicating that the strength and toughness of the steel in each embodiment not only meet the design requirements, but also have a certain margin. The fatigue performance test was carried out under a conventional environment using an Instron 8802 fatigue testing machine, the loading mode was tension-compression fatigue, the stress ratio Rs = -1, the test frequency was 20 Hz, and the fatigue life number under the peak stress of 560 MPa load was greater than 2 million times. According to the test method specified in GBT19746-2005, the invention steel was subjected to a 168-hour periodic immersion rapid corrosion evaluation test, and the weight loss method was used to evaluate the corrosion resistance of the invention steel, and the annual average corrosion rate was converted to 0.085 to 0.096 mm / a.

[0063] It is clear here that the examples listed are intended to illustrate the technical concept and main features of the present invention, and are not intended to be a limiting description of the invention. Any equivalent substitution or improvement that does not deviate from the essence of the present invention shall be deemed to be included in the protection scope of the present invention.

Claims

1. A GPa-level ultra-high strength fatigue-resistant marine engineering steel, characterized in that: The chemical composition of the steel plate is as follows: C: 0.02% ~ 0.07%, Si: 0.10% ~ 0.25%, Mn: 1.75% ~ 2.50%, P: 0.022% ~ 0.026%, S: ≤ 0.008%, Nb: 0.03% ~ 0.04%, V: 0.09% ~ 0.15%, Ti: 0.045% ~ 0.055%, Mo: 0.50% ~ 0.80%, Cr: 2.00% ~ 2.40%, Ni: 8.0% ~ 10.0%, Co: 8.0% ~ 12.0%, Als: 0.035% ~ 0.045%, N: 0.013% ~ 0.014%, Cu: 0 .58%~0.62%, Sb: 0.03%~0.05%, RE: 0.03%~0.05%, B: 0.0008%~0.001%, among which 0.08≤(Nb+V+Ti) / Mn≤0.12, 2.5≤Si / Al≤7.0, 3.5≤(Cu+Co) / Cr≤5.5, 12Cr / Co≥2.2, 3.2≤Ni / Cr≤4.5, 36Nb / Mn≥0.5, (Nb+V+Ti+Als) / N≥15, Ni / Cu≥13, (Nb+V+Ti) / RE≥4.2, RE / P≥1.10, and the rest are Fe and unavoidable impurities.

2. The GPa-level ultra-high strength fatigue-resistant marine engineering steel according to claim 1, characterized in that: The maximum thickness of the finished steel plate can reach 100mm.

3. The GPa-level ultra-high strength fatigue-resistant marine engineering steel according to claim 1, characterized in that: The yield strength of the steel is between 1080 and 1120 MPa, the elongation is ≥18%, the peak stress is 560 MPa, the fatigue life is greater than 2 million times, and the impact energy at -60°C is ≥150J.

4. The GPa-level ultra-high strength fatigue-resistant marine engineering steel according to claim 1, characterized in that: The corrosion rate of marine atmosphere is less than 0.10mm / a.

5. A method for producing GPa-level ultra-high strength fatigue-resistant marine engineering steel according to any one of claims 1 to 4, comprising smelting, slab continuous casting, rapid cooling of the ingot, heating of the ingot, rolling, double quenching and tempering heat treatment, characterized in that: The continuous casting billet drawing speed is controlled at 0.8~1.2m / min, and the secondary cooling water volume is 0.80~1.0m 3 / t, the reduction is 15.0-20.0mm; the continuous casting billet is rapidly cooled and the start cooling temperature is 950-1000℃, the cooling rate is 9.0-12.0℃ / s, and after cooling to 720-750℃, it enters the slow cooling pit for slow cooling, and then cools to below 150℃ at a cooling rate of 3.0-10.0℃ / h; the billet is heated by a segmented heating process, and the furnace temperature is 600-650℃. It is put into the furnace and kept warm for 2.0-3.0h. Below 950℃, a slow heating process is adopted, and the thermal rate is controlled at 6-8℃ / min. It is heated to 950℃ and kept warm for 30-40min. Above 950℃, a rapid heating process is adopted with an appropriately extended holding time, and the heating rate is controlled at 12-20℃ / min. It is heated to 1 The casting is rolled into a finished steel plate in two stages. The first stage adopts a high-temperature slow rolling and large reduction process. The rolling speed is 0.80-1.00 m / s. The reduction of each of the first three passes is ≥35 mm. During the rolling process, the mill cooling water is used for cooling between each pass. The final rolling temperature is 1000-1030 ° C. The thickness of the warm billet is 1.5-2.0 times the thickness of the finished product. The cooling rate is 8.0-10.0 ° C / s. It is cooled to 15-25 ° C above the second stage rolling temperature. The second stage rolling temperature is 880-900 ° C, the rolling speed is 1.2-1.6 m / s, the final rolling temperature is 810-840 ° C, and then air-cooled to room temperature.

6. The method for producing GPa-level ultra-high strength fatigue-resistant marine engineering steel according to claim 5, characterized in that: During the smelting process, 1.95-3.25 kg / ton steel of 20% rare earth alloy is added to the LF furnace 7-9 minutes before the end of vacuum treatment in the LF furnace, and then argon is blown for 5-10 minutes; then RH treatment is carried out, the RH treatment time is 30-35 minutes, and nitrogen is blown throughout the RH treatment, and [H] in the steel is controlled to be ≤1.0ppm, [O] ≤20ppm, and the net circulation time before removal is 6-10 minutes. Sb element is added before the end of RH treatment, and the added amount is ensured to be 1.2-1.3 times the target control amount.

7. According to the production method of GPa-level ultra-high strength and fatigue-resistant marine engineering steel as described in claim 5, the steel plate is subjected to two quenching and tempering heat treatments after rolling, the first quenching temperature is 870-900°C, the holding time is 1.2-1.5 min / mm, the second quenching temperature is 840-860°C, the holding time is 1.5-2.0 min / mm, the tempering temperature is 540-580°C, and the holding time is 2.5-3.5 min / mm.

Citation Information

Patent Citations

  • 165 Ksi-grade high-strength high-toughness corrosion-resistant steel and preparation method and application thereof

    CN111647815A

  • Corrosion-resistant steel for holds of coal carrying vessels or ore / coal carrying vessels, and hold

    CN112272712A

  • Seawater corrosion fatigue resistant ultrahigh-strength maritime work steel with high ductility and manufacturing method of seawater corrosion fatigue resistant ultrahigh-strength maritime work steel

    CN117660837A

  • Marine atmosphere corrosion resisting and seawater splashing corrosion resisting f690 steel plate with a thickness of 210 mm and easy to weld

    WO2018095085A1

  • Chain steel for use in mine and manufacturing method therefor

    WO2021169941A1

Cited By

  • Extra-thick ocean engineering steel capable of resisting fatigue crack propagation and manufacturing method of extra-thick ocean engineering steel

    CN120485663A

  • Steel plate for 1200MPa-grade marine environment ore conveying pipeline and production method of steel plate

    CN120738565A

  • A 1200mpa grade steel plate for marine environment mineral conveying pipeline and a production method thereof

    CN120738565B

  • High-strength weather-proof reinforcing steel bar and preparation method thereof

    CN121272293A

  • High-strength weather-resistant reinforcing bar and method for manufacturing the same

    CN121272293B